Women's Empowerment Metric for National Statistical Systems (WEMNS) - International Food Policy Research Institute; Emory University; World Bank; Oxford University; National Statistical Office, Malawi; Data Analysis and Technical Assistance (DATA) Limited; Vox Latina, Guatemala; Interdisciplinary Analysts, Nepal (International Food Policy Research Institute, 2024)
The Women’s Empowerment Metric for National Statistical Systems (WEMNS) is a streamlined tool for measuring empowerment. It is intended for use in large-scale, multitopic surveys in both rural and urban areas and is relevant across a wide range of livelihood strategies. WEMNS was developed by the International Food Policy Research Institute (IFPRI), Emory University, Oxford University, and the World Bank’s Living Standards Measurement Study Unit in collaboration with country partners in Bangladesh, Guatemala, Malawi, and Nepal . This work was funded by the Bill & Melinda Gates Foundation and the United States Agency for International Development.